The FUTURE of the US Marine Seafloor and Subseafloor Sampling Capabilities - FUTURE 2024 PI‐team; Bruce Appelgate; Brandon Dugan; Nobuhisa Eguchi; Daniel Fornari; Tim Freudenthal; Patrick Fulton; Sean Kelley; Susan Q. Lang; Dana Manalang; Alan Mix; Rick Trask; et al. (AGU Advances)
Abstract Recent changes in US oceanographic assets are impacting scientists' ability to access seafloor and sub‐seafloor materials and thus constraining progress on science critical for societal needs. Here we identify national infrastructure needs to address critical science questions. This commentary reports on community‐driven discussions that took place during the 3‐day FUTURE of US Seafloor Sampling Capabilities 2024 Workshop, which used an “all‐hands‐on‐deck” approach to assess seafloor and sub‐seafloor sampling requirements of a broad range of scientific objectives, focusing on capabilities that could be supported through the US Academic Research Fleet (US‐ARF) now or in the near future. Cross‐cutting issues identified included weight and size limitations in the over‐boarding capabilities of the US‐ARF, a need to access material at depths greater than ∼20 m below the seafloor, sampling capabilities at the full range of ocean depths, technologies required for precise navigation‐guided sampling and drilling, resources to capitalize on the research potential of returned materials, and workforce development.